Peran Keakuratan Gambar Teknik terhadap Efisiensi Biaya Bangunan - Faqih, Muhammad Abdullah (Maliki Interdisciplinary Journal, 2025)
In the construction industry, technical drawings play a crucial role. They not only function as visual documents but also serve as a communication tool among various parties involved, such as architects, engineers, contractors, and clients. Through the proper use of technical drawings, the construction process can be carried out more efficiently. Technical drawings represent the plans and specifications of a building, encompassing essential details such as dimensions, materials, and construction procedures to be followed. With clear and detailed technical drawings, all involved parties can understand and adhere to the same plan, reducing the potential for misunderstandings that could lead to delays or unplanned changes. Cost efficiency in construction projects is significantly influenced by thorough planning processes. Accurate technical drawings enable the identification and resolution of issues early on, before the project begins. This journal provides an in-depth analysis of the role of technical drawings in construction cost efficiency. The findings indicate that technical drawings play a vital role in construction projects by preventing errors and design revisions, optimizing materials and time, ensuring efficient use of resources, and improving team coordination. All these roles of technical drawings contribute to building cost efficiency.